Spatial Dialogues of Historic Alley through Serial Vision Theory (Case Study: Pontocho Roji and Jalan Rukunan) - Wardhani, Mustika Kusumaning; Wang, Zhixi (MODUL, 2023)
Traditional settlements are part of the urban context of every country, especially tourism-oriented cities such as Yogyakarta (Indonesia) and Kyoto (Japan). The design strategy and regulations have a more significant and complex portion involving cultural heritage buildings and settlement networks that shape the city's morphology. Pontocho and Kotagede are cultural areas with unique characteristics, such as the existence of narrow allies called Roji (in Japanese) and 'Jalan rukunan'. This research aims to understand the role of alleyways between two traditional settlements that form urban identities. The descriptive-qualitative research method uses depth map software to display the observed area coverage through connectivity and visibility. The results found in this research can manifest both locations' characters in a tangible and intangible aspect. The existence of a historic alley that forms the morphology of historic settlements will keep its existence considered because it is a continuity network that creates a serial vision for observers, tourists, and also the local community. Spatial dialogue studies through serial vision theory in historic alleys are expected to provide renewal to considerations of revitalizing heritage settlements, especially in Asian countries.